2016
DOI: 10.1530/eje-15-1010
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, markers of subclinical inflammation and nerve conduction in individuals with recently diagnosed type 1 and type 2 diabetes

Abstract: Objective: Subclinical inflammation has been implicated in the development of diabetic sensorimotor polyneuropathy (DSPN), but studies using electrophysiological assessment as outcomes are scarce. Therefore, we aimed to investigate associations of biomarkers reflecting different aspects of subclinical inflammation with motor and sensory nerve conduction velocity (NCV) in individuals with diabetes. Design and methods: Motor and sensory NCV was assessed in individuals with recently diagnosed type 2 (nZ352) or ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 47 publications
3
39
1
Order By: Relevance
“…The second main finding of this study is the identification of higher serum levels of the proinflammatory cytokines IL-6 and TNF-a in individuals with incident DSPN compared with those without incident DSPN after adjustment for anthropometric or metabolic risk factors for DSPN. The finding for IL-6 not only corroborates the report from the KORA F4 study (8) but also is in line with other cross-sectional studies investigating DSPN or impaired nerve conduction (5,17). By contrast, associations between higher TNF-a and DSPN or its components have so far been limited to small studies that did not adjust for confounding factors (6,7,9,15,31), whereas no associations were found in studies that considered confounders (5,8).…”
Section: Il-6 Tnf-a and Incident Dspnsupporting
confidence: 88%
See 3 more Smart Citations
“…The second main finding of this study is the identification of higher serum levels of the proinflammatory cytokines IL-6 and TNF-a in individuals with incident DSPN compared with those without incident DSPN after adjustment for anthropometric or metabolic risk factors for DSPN. The finding for IL-6 not only corroborates the report from the KORA F4 study (8) but also is in line with other cross-sectional studies investigating DSPN or impaired nerve conduction (5,17). By contrast, associations between higher TNF-a and DSPN or its components have so far been limited to small studies that did not adjust for confounding factors (6,7,9,15,31), whereas no associations were found in studies that considered confounders (5,8).…”
Section: Il-6 Tnf-a and Incident Dspnsupporting
confidence: 88%
“…The inverse association between adiponectin and DSPN in the age-and sex-adjusted model in our study is also interesting because cross-sectional studies reported associations between higher adiponectin and DSPN and/or impaired nerve conduction (10,11,17). This discrepancy suggests some degree of residual confounding or reverse causality in the latter analyses, which seems to be no longer relevant in studies using a prospective design.…”
Section: Il-6 Tnf-a and Incident Dspnmentioning
confidence: 53%
See 2 more Smart Citations
“…Serum concentrations of high-sensitivity C-reactive protein (hsCRP), IL-6, IL-18, total and high-molecular-weight (HMW) adiponectin, soluble intercellular adhesion molecule-1 (sICAM-1) and soluble E-selectin (sE-selectin) were measured as described 9 10…”
Section: Methodsmentioning
confidence: 99%